Approximate Preservers on Banach Algebras and C*-Algebras - M. Burgos; A. C. Márquez-García; A. Morales-Campoy (Abstract and Applied Analysis)
The aim of the present paper is to give approximate versions of Hua’s theorem and other related results for Banach algebras and C*-algebras. We also study linear maps approximately preserving the conorm between unital C*-algebras.